The Influence of Motivational English Anti-Smoking Messages, EFL Communication Self-Efficacy, and Health Communication Motivation on Smoking Refusal Intention Among Senior High School Students in Pekanbaru City - Fauzi Enny; Hendra Setyawan (PT FORMOSA CENDEKIA GLOBAL, 2026)
Adolescent smoking remains a critical school health issue because refusal of smoking invitations is shaped by health messages, communication beliefs, and peer social pressure. This study examined the influence of motivational English anti-smoking messages, EFL communication self-efficacy, and health communication motivation on smoking refusal intention among senior high school students in Pekanbaru City. A quantitative correlational-explanatory approach with a cross-sectional survey was applied to 100 students using a four-point Likert questionnaire. The instrument consisted of four constructs, each comprising 16 items. Validity was tested using Pearson Product Moment correlation, reliability was assessed using Cronbach’s Alpha, and hypotheses were examined through multiple linear regression. All items were valid, with r values greater than 0.197, and very high reliability was obtained for all constructs, namely X1 = 0.968, X2 = 0.970, X3 = 0.972, and Y = 0.973. The model was significant, F(3,96) = 75.818, p < 0.001, R = 0.839, and R² = 0.703. Health communication motivation was the only significant partial predictor of smoking refusal intention (B = 0.588, β = 0.585, p < 0.001), whereas motivational English anti-smoking messages and EFL communication self-efficacy showed positive but non-significant effects. These findings highlight the importance of strengthening health communication motivation so that health messages and language competence can be transformed into actual refusal readiness.